HYBRID MODELING OF OPEN LOOP DC-DC CONVERTERS - Zulueta,Ekaitz (Universidad de Tarapacá. Facultad de Ingeniería, 2003)
Power electronic converters always have been circuits of difficult modelling because differential equations that describe them have discontinuities. Although this situation has been improved since the appearance of the Hybrid Systems theory, able to jointly describe both continuous and discrete behaviors exhibited by some physical systems, nowadays it is possible to obtain very precise models which help us in the study and design of such circuits. An excellent option for the discrete part model (reactive system) is to use statecharts, since this powerful language has recently been implemented and named Stateflow as a part of the Simulink toolbox of Matlab. So, today, the complete modeling of some hybrid systems within Matlab environment is possible. In this work the open loop hybrid modeling and simulation of the well-known dc-dc converters named buck and boost, using Matlab-Simulink-Stateflow, is presented